THE EFFECTIVENESS OF RANSOM NOTE GAME IN LEARNING VOCABULARY AT SMPN 1 KERUAK - Arbi Maulida Hadijah Zurri; Kamarudin Kamarudin; Ahmad Hanan (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2017)
This research was aimed at finding out the effectevenness of Ransom Note Game in learning vocabulary. this research was quasi experimental design. The populations of this research were all of students at second grade students of SMPN 1 KERUAK that consist of 284 students that consist of eight different classes. In which the sample of this research used two classes where VIII.1 Class as experimental group consisted of 32 student and VIII.3 as control group consisted of 31 students. The experimental was taught by Ransom Note Game Game and control group taught by Puzzle Game. The instruments that used were objective test with multiple choices, matching word, fill in the blank and true or false. The analysis used t-test formula. The result of the analysis, showed that the value of to (t obtained) 2, 0888 was higher than tt (t table) 1, 8702, the significant level 0, 05. Based on the result of this investigation, it was proved that the alternative hypothesis (Ha) was accepted. In other words, there was significant effect of Ransom Note Game in learning vocabulary at the second grade students at SMPN 1 KERUAK in academic year 2016/2017.